Transparent glass ceramic, toughened glass ceramic and preparation method and application thereof
By optimizing the raw material ratio and heat treatment process in glass ceramics, transparent glass ceramics with high strength and drop resistance are formed, and their mechanical properties are improved through chemical strengthening, the problems of insufficient performance of traditional glass cover sheet materials and high cost of LAS systems are solved, and the application of efficient and economical glass ceramic materials is achieved.
Patent Information
- Application Number
- CN202411911832.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-25
AI Technical Summary
The mechanical strength and drop resistance of traditional glass cover materials are poor, and the LAS system glass ceramics with lithium as the main element are expensive, which limits its market application.
A transparent glass ceramic formula is adopted, including SiO2, Al2O3, Na2O, K2O, Li2O, B2O3, ZrO2, TiO2, P2O5, MgO, CaO and SnO2, and through specific raw material ratios and heat treatment processes, glass ceramics with high strength and drop resistance are formed, and its mechanical properties are improved through two chemical strengthenings.
It achieves the realization of significantly improving the mechanical and thermal shock properties of glass ceramics while ensuring optical performance, reducing production costs, and expanding its application scenarios in consumer electronic products and vehicle display screens.
Smart Images

Figure CN119683859A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of glass ceramics, and in particular to transparent glass ceramics, reinforced glass ceramics, and preparation methods and applications thereof. Background Art
[0002] With the increasing development of the fifth generation of mobile communication technology and new energy smart cars, the portability and thinness of consumer electronic products and vehicle-mounted display devices have gradually become the mainstream trend in the market. The use environments of portable electronic devices (such as watches, tablets, mobile phones, notebooks and cameras, etc.) and vehicle-mounted display devices are diversified, and they often hit the surface of the device display area in different use environments, causing partial damage to the device display components and reducing the service life of the device. At the same time, in order to reduce the overall weight of the vehicle and improve the battery life efficiency, new energy smart cars also need to reduce the overall weight of the display devices they carry to save energy.
[0003] Therefore, it is necessary to ensure that the outermost cover glass of the electronic device or vehicle-mounted display device can withstand higher mechanical impact energy while reducing the glass thickness (i.e. reducing the weight of the display device), and also needs to have excellent optical properties to meet the performance requirements of the display device.
[0004] As a traditional cover material, high (lithium) aluminosilicate glass cannot significantly improve its mechanical strength simply through scientific strengthening technology due to the glass formula, resulting in poor drop resistance and scratch resistance. Therefore, it is necessary to develop transparent glass-ceramic materials with high strength and drop resistance to meet the application requirements of ultra-thin mobile phone covers.
[0005] At the same time, the main crystal form of the currently more popular transparent glass-ceramics is the LAS system with lithium Li as the main element, which requires a large amount of lithium-containing compounds. Li is an important component of the latest new energy storage materials, and the cost of lithium-containing compounds is high, such as lithium carbonate. As a result, the cost of LAS system transparent glass-ceramics remains high, which is not conducive to the market application of transparent microcrystalline glass materials.
[0006] Therefore, the prior art still needs to be improved and developed. Summary of the invention
[0007] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide transparent glass ceramics, reinforced glass ceramics and preparation methods and applications thereof, aiming to solve the problems of poor mechanical strength and drop resistance of traditional glass cover materials and high cost of LAS system glass ceramics.
[0008] The technical solution of the present invention is as follows:
[0009] In a first aspect of the present invention, a transparent glass ceramic is provided, wherein the transparent glass ceramic comprises the following raw materials in terms of molar percentage:
[0010] SiO2 42.0-52.0%;
[0011] Al2O3 12.0-23.5%;
[0012] Na2O 15.0-23.5%;
[0013] K2O 0-1.0%;
[0014] Li2O 3.0-9.0%;
[0015] B2O3 3.0-8.0%;
[0016] ZrO2 0.5-2.0%;
[0017] TiO2 0-1.0%;
[0018] P2O5 1.0-3.0%;
[0019] MgO 0.5-2.0%;
[0020] CaO 0-2.0%;
[0021] SnO2 0.1-0.5%;
[0022] At least one of the following relationships must also be satisfied:
[0023] 1) 75% ≤ Al2O3 / Na2O ≤ 100%;
[0024] 2)20%≤(Na2O+Li2O)≤30%;
[0025] 3)2.0%≤(ZrO2+TiO2+P2O5)≤6.0%;
[0026] The linear thermal expansion coefficient α of the transparent glass ceramic in the temperature range of 0°C-300°C is ≤100*10 -7 ℃-1.
[0028] Optionally, the raw material of the transparent glass-ceramic further includes 0.1-1.0% of a clarifier, and the clarifier includes at least one of NaCl, Sb2O3, As2O3, nitrate, and sulfate.
[0029] Optionally, the transparent glass-ceramic has crystals with an average grain size ranging from 30 to 70 nm and a crystallinity of 25 to 55%; the crystal phases of the crystals are one or more of sodium nepheline, triclinic nepheline, sodium silicate and zirconium oxide.
[0030] A second aspect of the present invention provides a method for preparing a reinforced glass ceramic, comprising the following steps:
[0031] S1. Mixing, melting, clarifying, molding and annealing the raw materials of the transparent glass-ceramic according to a proportion to obtain a base glass, wherein the molding method is selected from one of a float method, an overflow method, a roller pressing method and a continuous melting casting method;
[0032] S2, performing nucleation and crystallization treatment on the base glass to obtain transparent glass ceramics, wherein the nucleation temperature is 500-545° C., and the nucleation time is 120-360 min; the crystallization temperature is 600-700° C., and the crystallization time is 15 min-120 min;
[0033] S3, shaping, cutting, grinding and polishing the transparent glass ceramic to obtain a glass ceramic sheet, and immersing the glass ceramic sheet in molten nitrate for chemical strengthening twice to obtain the strengthened glass ceramic;
[0034] The two chemical strengthening steps include:
[0035] The glass ceramic sheet is placed in a mixed molten salt of NaNO3 and / or KNO3 in a molten state at 420-480°C and immersed for 2-10 hours to obtain a first chemically strengthened glass ceramic; and the first chemically strengthened glass ceramic is placed in a molten salt of KNO3 in a molten state at 380-420°C and immersed for 15-60 minutes to obtain the strengthened glass ceramic.
[0036] The third aspect of the present invention provides a reinforced glass-ceramic prepared by the preparation method of the reinforced glass-ceramic.
[0037] Optionally, the depth of the surface stress layer DOL of the reinforced glass-ceramic is 110μm≤DOL≤175μm; the surface compressive stress CS of the transparent glass-ceramic is greater than 700MPa, and the CS_50 value is greater than or equal to 450Mpa; the four-point bending strength M of the reinforced glass-ceramic is greater than or equal to 750MPa.
[0038] Optionally, when the thickness of the reinforced glass ceramic is less than 1 mm, the transmittance of visible light of 400 nm to 780 nm is greater than or equal to 86%, the haze is less than or equal to 0.18%, and the B value range in the Lab color model is: 0.60≤|B|≤1.0.
[0039] Optionally, the maximum extrusion pressure that the reinforced glass-ceramic can withstand is ≥15Kgf.
[0040] Optionally, when the thickness of the reinforced glass-ceramic is 0.70 mm, under the condition of 80-grit sandpaper and directional impact with a load of 200 g, it can withstand a height of ≥180 cm and an impact energy of ≥0.30 joule.
[0041] A fourth aspect of the present invention provides an application of the tempered glass ceramic in consumer electronic products or vehicle-mounted display screens.
[0042] Beneficial effects:
[0043] The transparent glass ceramic provided by the present invention has Na as the main element of the crystal phase, and is a Na2O-Al2O3-SiO2 (NAS) glass ceramic. The reinforced glass ceramic obtained by chemically strengthening the transparent glass ceramic has excellent optical properties and mechanical properties, and can meet the optical properties and mechanical properties required by electronic consumer products and vehicle-mounted display device screen protection cover materials, and also has excellent thermal shock resistance. Compared with the existing LAS system glass ceramics with Li as the main element of the crystal phase, the use cost is reduced and the application scenarios of glass ceramics are greatly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 This is a sample picture of the base glass of Example 1 of the present invention.
[0045] Figure 2 The XRD spectrum of the transparent glass ceramic of Example 1 of the present invention is a sodium nepheline crystal phase. DETAILED DESCRIPTION
[0046] The present invention provides transparent glass ceramics, reinforced glass ceramics and preparation methods and applications thereof. To make the purpose, technical scheme and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0047] Unless otherwise defined, all technical terms and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0048] In order to better understand the content of the present invention, some terms in the present invention are explained:
[0049] Basic glass: Glass that has not been nucleated, crystallized or chemically strengthened by ion exchange is prepared by uniformly mixing compounds containing various oxides (including silicon dioxide, aluminum oxide, sodium oxide, calcium oxide, etc.), melting them at high temperature, and then forming them by one of the following methods: float process, overflow down-draw process, roller pressing process or casting process.
[0050] Glass ceramics: also known as microcrystalline glass, is a type of solid composite material that contains both glass phase and crystal phase (microcrystalline phase, crystalline phase) and is prepared by subjecting base glass to a targeted controlled crystallization treatment.
[0051] Nucleation: The base glass is heat treated to make the nucleating material in the glass grow tiny crystal nuclei.
[0052] Crystallization: The base glass is grown into a certain crystal based on the crystal nucleus through heat treatment.
[0053] Crystalline phase: The microscopic structure of a crystal is a general term for a large number of crystalline solid phase components.
[0054] Crystallinity: It is used to indicate the proportion of the crystalline region in glass ceramics, generally based on the volume ratio of the crystal phase in the entire glass ceramics.
[0055] CTE linear thermal expansion coefficient α value: English is coefficient of thermal expansion, referred to as CTE, refers to the expansion and contraction of an object due to temperature changes. Its change ability is expressed by the change in length value caused by unit temperature change under constant pressure (p constant), that is, the thermal expansion coefficient. The linear expansion coefficient refers to the ratio of the change in length of a solid substance in a certain direction when the temperature changes by 1 degree Celsius to its length at 20℃ (i.e. standard laboratory environment).
[0056] Thermal shock resistance of glass materials: refers to the ability of glass ceramics to withstand rapid changes in temperature, and is an important indicator for measuring the performance of refractory materials.
[0057] The embodiment of the present invention provides a transparent glass ceramic, which comprises the following raw materials in molar percentage:
[0058] SiO2 42.0-52.0%;
[0059] Al2O3 12.0-23.5%;
[0060] Na2O 15.0-23.5%;
[0061] K2O 0-1.0%;
[0062] Li2O 3.0-9.0%;
[0063] B2O3 3.0-8.0%;
[0064] ZrO2 0.5-2.0%;
[0065] TiO2 0-1.0%;
[0066] P2O5 1.0-3.0%;
[0067] MgO 0.5-2.0%;
[0068] CaO 0-2.0%;
[0069] SnO2 0.1-0.5%;
[0070] At least one of the following relationships must also be satisfied:
[0071] 1) 75% ≤ Al2O3 / Na2O ≤ 100%;
[0072] 2)20%≤(Na2O+Li2O)≤30%;
[0073] 3)2.0%≤(ZrO2+TiO2+P2O5)≤6.0%;
[0074] The linear thermal expansion coefficient α of the transparent glass ceramic in the temperature range of 0°C-300°C is ≤100*10 -7 ℃-1.
[0076] Among the above raw material components, the present invention uses SiO2 as one of the main components of the network oxide of the basic glass and glass ceramic materials, which is one of the important components that constitute the Si-O tetrahedron in the main body and form the network structure. The molar proportion of SiO2 is 42.0-52.0%, preferably 48-52%, for example, it can be 42.0%, 43.0%, 44.0%, 45.0%, 46.0%, 47.0%, 48.0%, 49.0%, 50.0%, 51.0% and 52.0% and any one of the components in the range of any two of the above values. When the SiO2 content is too low, the product made of the material has poor resistance to devitrification, poor scratch resistance and low hardness; when the SiO2 content is greater than 52.0%, the melting temperature of the basic glass is too high, and the composition and size of the precipitated crystals after heat treatment are difficult to control.
[0077] Al2O3 and Na2O are components that form the main crystal forms of sodium pyroxene, triclinic pyroxene, etc. in the transparent glass ceramics. The molar ratio of the two is 75%≤Al2O3 / Na2O≤100%. If the ratio of the two is outside this range, it is difficult to form controllable sodium pyroxene, triclinic pyroxene, etc. crystals. Among them, Al2O3 is one of the main components of the internal network structure of the basic glass and glass ceramic materials, and is also the main component of the crystal forms of sodium pyroxene, triclinic pyroxene, etc. It can significantly improve the thermal stability and ion exchange performance, and is helpful to generate the target crystal. The molar percentage of Al2O3 is 12.0-23.5%, preferably 12.0-22.0%, for example, it can be 12.0%, 13.0%, 14.0%, 15.0%, 16.0%, 17.0%, 18.0%, 19.0%, 20.0%, 21.0%, 22.0%, 23.5% and any value between any two of the above percentages. However, when the Al2O3 content exceeds 23.5%, it is easy to cause the transmittance to decrease and the high temperature viscosity to increase, and the melting point to increase, which is not conducive to production.
[0078] Na2O and Li2O are important alkali metals in glass ceramics. Both alkali metal oxides are effective glass fluxes, which can significantly reduce the melting temperature of the base glass. The total molar ratio of the two alkali metal oxides satisfies the relationship of 20%≤(Na2O+Li2O)≤30%. The total molar ratio of the two alkali metal oxides outside this range has a greater impact on the internal O-Si-O bond and has a significant impact on the formation of the transparent glass ceramics. If the total molar ratio of the two alkali metal oxides is too high or too low, it will be difficult to control the formation of major crystal forms such as sodium nepheline and triclinic nepheline. At the same time, Na + and Li + The properties of the two alkali metal elements play different roles in the transparent glass-ceramics: Na + It is sodium nepheline (NaAlSiO4), triclinic nepheline (Na 7.85 Al 7.85 Si 8.15 O 32) and is also an important element that participates in ion exchange during chemical strengthening of glass ceramic materials. However, when the Na2O content is higher than 26.5%, the chemical stability is significantly reduced. Therefore, the ideal Na2O molar percentage should be less than or equal to 23.5%, which can keep the melting temperature within a suitable range and ensure good ion exchange properties. The molar percentage of Na2O ranges from 15.0 to 23.5%, preferably from 15.0 to 22.5%, and can be specifically 15.0%, 16.0%, 17.0%, 18.0%, 19.0%, 20.0%, 21.0%, 22.0%, 23.0%, 23.5% and any value between any two of the above percentages.
[0079] Li2O is an oxide with high alkali metal activity and is an external oxide of the glass network. As one of the additives to reduce the high temperature viscosity of the base glass, it significantly improves the high temperature fluidity of the base glass. + It can participate in ion exchange chemical strengthening reaction to further enhance the mechanical properties of glass ceramics. The molar percentage of Li2O is in the range of 3.0-9.0%, preferably 4.0-9.0%, and in specific embodiments, it can be 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%, 7.0%, 7.5%, 8.0%, 8.5% and 9.0%, and any value between any two of the above percentage values.
[0080] K2O can reduce the high temperature viscosity of the base glass, significantly improve the formability and fluidity of the base glass at high temperature, and significantly reduce the incidence of cracks. Adding a small amount of K2O can slow down the crystallization behavior that occurs during glass molding, but when the molar ratio of K2O is too high, exceeding 1.0%, crystalline phases such as potassium feldspar will be generated, which will harm the mechanical strength and optical properties. The molar ratio of K2O in the raw material components of the transparent glass ceramics in the present invention is in the range of 0.0 to 1.0%, preferably 0.0 to 0.5%, and can be specifically 0, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% and 1.0%, and any value between any two of the above values.
[0081] B2O3 is a network exosome oxide of glass. Its cation has a larger ionic radius and a higher coordination number (6.8) and is generally filled in the gap of the silicon-oxygen tetrahedral framework. Its cation coordination rarely changes, and some properties of its oxide can be considered as constant. B2O3 helps to provide a basic glass with a low melting temperature. In addition, adding B2O3 to the basic glass can also improve the thermal properties of glass-ceramics and affect the thermal shock properties of subsequent heat treatment of glass-ceramics. When the boron in the residual glass is not balanced by the charge of the alkaline oxide or the divalent cation oxide, the boron will be in a triangular-coordinated state (or a triply coordinated boron), which opens the glass structure, and the network around the triply coordinated boron is not as rigid as the network of the tetrahedral coordinated (or quadruple coordinated) boron. The presence of boron in the residual glass (and the basic glass) of the glass-ceramics will reduce the viscosity of the residual glass-ceramics (or the basic glass), which will promote the growth of sodium nepheline and triclinic nepheline crystals, especially the growth of larger crystals with a higher aspect ratio. Generally speaking, the amount of boron should be controlled to maintain the chemical durability and mechanical strength of the ceramicized bulk glass ceramics, especially B2O3 can have a significant impact on the thermodynamic properties of the base glass and the thermal shock properties of the glass ceramics. At the same time, too high or too low B2O3 content is unstable for the chemical resistance of the glass ceramic material formed after the base glass nucleation and crystallization. In the raw material components used in the preparation of transparent glass ceramics of the present invention, the molar percentage of B2O3 content ranges from 3.0-8.0%, preferably 3.0-7.0%, and specifically can be 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%, 7.0%, 7.5% and 8.0% and any value between any two of the above values.
[0082] The three oxides ZrO2, TiO2 and P2O5 are important nucleating agents for crystal production in glass-ceramic materials. The total molar proportion of these three nucleating agents is 2.0%≤(ZrO2+TiO2+P2O5)≤6.0%. Since the three glass-ceramic nucleating agents have different nucleating abilities, their corresponding molar proportions are different.
[0083] Among them, ZrO2 can significantly reduce the devitrification of glass and lower the liquidus temperature to improve the stability of transparent glass ceramics. At high temperatures, ZrSiO4 can form a main liquidus phase, which significantly reduces the liquidus viscosity. When the glass contains no more than 2% molar percentage of ZrO2, transparent glass can be formed. At the same time, the tetragonal crystal form of ZrO2 can increase the strength and toughness of glass ceramics; the molar percentage range of ZrO2 in the present invention is 0.5-2.0%, specifically 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0% and any value between any two of the above values.
[0084] Ti in TiO2 4+ Body-centered octahedral structural unit, 6 O 2- Coordinated in six directions, containing 1 Ti 4+ The oxygen octahedron can effectively promote the growth of crystal nuclei in the base glass during the nucleation crystallization heat treatment process, and at the same time improve the stability of the glass; the introduction of TiO2 effectively promotes the precipitation of crystal nuclei in the nucleation process, and at the same time, the introduction of TiO2 easily causes phase separation in the base glass, resulting in crystallization, affecting the formation of the glass. The molar ratio of TiO2 in the raw material components of the present invention is in the range of 0 to 1.0%, specifically 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0% and any value between any two of the above values.
[0085] P2O5 can promote the phase separation and overall crystallization ability of the base glass. If the P2O5 concentration is too low, the base glass will not crystallize, and will only form crystals from the surface to the inside at a higher temperature and lower viscosity. If the P2O5 concentration is too high, it will be difficult to control devitrification when cooling during the base glass formation process. The molar proportion of P2O5 in the raw material components of the present invention is in the range of 1.0 to 3.0%, specifically 1.0%, 1.50%, 2.0%, 2.5%, 3.0% and any value between any two of the above values.
[0086] MgO, as a divalent alkaline earth metal, can effectively break the bridging oxygen bond of Si-O tetrahedron inside the base glass. 2+ It is beneficial to promote the glass to have a lower refractive index and density in the tetrahedron. The molar ratio of MgO content in the raw material components of the present invention is in the range of 0.5-2.0%, specifically 0.50%, 1.0%, 1.50%, 2.0% and any value in the range of any two of the above values.
[0087] As a divalent alkaline earth metal, CaO can promote the crystallization ability of the base glass. 2+ It is beneficial to improve the optical properties of glass such as refractive index and transmittance. The molar ratio of CaO in the raw material components of the present invention ranges from 0.0% to 2.0%, and can be specifically selected as 0%, 0.50%, 1.0%, 1.5%, 2.0% and any value between any two of the above values.
[0088] SnO2 is an effective clarifier for base glass. Its introduction is beneficial to reducing the formation of gas defects in the glass melt, reducing the number of bubbles in the melt, and improving the clarification effect. The molar percentage range of SnO2 in the present invention is 0.1-0.5%, specifically 0.1%, 0.2%, 0.3%, 0.4%, 0.5% and any value in the range of any two of the above values.
[0089] In some embodiments, the raw material of the transparent glass-ceramic further includes 0.1-1.0% of a clarifier, and the clarifier includes at least one of NaCl, Sb2O3, As2O3, nitrate, and sulfate.
[0090] The clarifier can homogenize the oxides in the glass ceramic raw material in a molten state, thereby evenly distributing the oxides in the glass body. The molar proportion of the clarifier in the present invention can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0% and values between any two of the above values.
[0091] In some embodiments, the transparent glass-ceramic has crystals with an average grain size ranging from 30 to 70 nm and a crystallinity of 25 to 55%; the crystal phases of the crystals are one or more of sodium nepheline, triclinic nepheline, sodium silicate and zirconium oxide.
[0092] The present invention provides a method for preparing a reinforced glass ceramic, comprising the following steps:
[0093] S1. Mixing, melting, clarifying, molding and annealing the raw materials of the transparent glass-ceramic according to a proportion to obtain a base glass, wherein the molding method is selected from one of a float method, an overflow method, a roller pressing method and a continuous melting casting method;
[0094] S2, performing nucleation and crystallization treatment on the base glass to obtain transparent glass ceramics, wherein the nucleation temperature is 500-545° C., and the nucleation time is 120-360 min; the crystallization temperature is 600-700° C., and the crystallization time is 15 min-120 min;
[0095] S3, shaping, cutting, grinding and polishing the transparent glass ceramic to obtain a glass ceramic sheet, and immersing the glass ceramic sheet in molten nitrate for chemical strengthening twice to obtain the strengthened glass ceramic;
[0096] The two chemical strengthening steps include:
[0097] The glass ceramic sheet is placed in a mixed molten salt of NaNO3 and / or KNO3 in a molten state at 420-480°C and immersed for 2-10 hours to obtain a first chemically strengthened glass ceramic; the first chemically strengthened glass ceramic is then placed in a molten salt of KNO3 in a molten state at 380-420°C and immersed for 15-60 minutes for a second chemical strengthening to obtain the strengthened glass ceramic.
[0098] The embodiment of the present invention provides a reinforced glass ceramic, which is prepared by the preparation method of the reinforced glass ceramic.
[0099] In some embodiments, the depth DOL of the surface stress layer of the strengthened glass-ceramic is 110 μm≤DOL≤175 μm; the surface compressive stress CS of the transparent glass-ceramic is greater than 700 MPa, and the CS_50 value is greater than or equal to 450 MPa.
[0100] In some embodiments, the four-point bending strength M of the reinforced glass-ceramic is greater than or equal to 750 MPa.
[0101] In some embodiments, when the thickness of the reinforced glass-ceramic is less than 1 mm, the transmittance of visible light of 400 nm to 780 nm is greater than or equal to 86%, the haze is less than or equal to 0.18%, and the B value range in the Lab color model is: 0.60≤|B|≤1.0.
[0102] In some embodiments, the maximum extrusion pressure that the reinforced glass-ceramic can withstand is ≥15 Kgf.
[0103] In some embodiments, when the thickness of the reinforced glass-ceramic is 0.70 mm, under the condition of 80-grit sandpaper and directional impact with a load of 200 g, the glass-ceramic can withstand a height of ≥180 cm and an impact energy of ≥0.30 joule.
[0104] An embodiment of the present invention provides an application of the tempered glass ceramic in consumer electronic products or vehicle-mounted display screens.
[0105] The following describes it in detail through specific embodiments.
[0106] Example 1
[0107] (1) Preparation of basic glass: The oxide components in the raw materials are uniformly mixed, melted in a platinum-rhodium alloy crucible at 1560°C for 4 hours, stirred during the melting process, and then poured into a mold composed of steel bars and steel blocks in a high-temperature molten state of 1450°C to form a rectangular glass brick, which is annealed to obtain a block-shaped basic glass brick. The basic glass sample prepared in this step is as follows Figure 1 shown.
[0108] (2) Preparation of transparent glass ceramics: The basic glass bricks obtained in step (1) are placed in a precision crystallization furnace or a tunnel kiln for heat treatment of nucleation and crystallization to obtain transparent glass ceramics.
[0109] (3) Preparation of strengthened glass ceramics: The transparent glass ceramics obtained in step (2) are shaped, cut, and polished to obtain glass ceramic sheets of 50 mm*50 mm*0.7 mm in size. The glass ceramic sheets are placed in molten nitrate for chemical strengthening twice:
[0110] Firstly, the glass ceramic sheet is placed in a mixed molten salt of NaNO3 and KNO3 (the mass ratio of NaNO3 to KNO3 is 99:1) in a molten state at 450° C. and immersed for 6 hours for a first chemical strengthening to obtain a first chemically strengthened glass ceramic;
[0111] Then, the first chemically strengthened glass-ceramic obtained was placed in pure KNO3 molten salt in a molten state at 395° C. and immersed for 30 minutes for a second chemical strengthening to obtain strengthened glass-ceramic.
[0112] Embodiment 2-7
[0113] The difference from Example 1 is that: the raw material formula is different; the process parameters of nucleation and crystallization in the preparation steps of transparent glass ceramics are different.
[0114] The raw materials used in the preparation of the basic glass in Examples 1-7 are shown in Table 1:
[0115] Table 1
[0116]
[0117]
[0118] The process parameters of nucleation and crystallization in the preparation steps of transparent glass-ceramics in Examples 1-7 are shown in Table 2 below.
[0119] Table 2
[0120]
[0121] The transparent glass-ceramics were subjected to the following tests:
[0122] 1. XRD test
[0123] The glass ceramic sheet was ground into glass fine powder by a grinding machine, and tested by Rigaku Smartlab X-ray diffraction (XRD) under the conditions of diffraction angle range 2θ of 10° to 80°, scanning speed of 10° / min, working voltage of 40kV, and working current of 30mA, and the XRD diffraction peak curve was obtained, as shown in FIG. Figure 1 shown.
[0124] The professional processing software Jade is used to analyze the XRD diffraction data, analyze the type, size and proportion of the crystal phase contained in the transparent glass-ceramics, and fit the diffraction peak curve to obtain the total content of the crystal phase in the transparent glass-ceramics.
[0125] 2. SEM test
[0126] The transparent glass-ceramics were tested using a FEI NOVA NANO scanning electron microscope (SEM) to observe the grain size and the morphology of the crystals precipitated in the transparent glass-ceramics. The EDS energy spectrum was used to analyze the proportion of each element in the transparent glass-ceramics and the corresponding crystal phase.
[0127] The crystal type, grain size and crystallinity of transparent glass-ceramics are shown in Table 3 below.
[0128] Table 3
[0129]
[0130] 3. Test of CTE coefficient of thermal expansion in the range of 0-300℃
[0131] The linear thermal expansion coefficient can be referred to as the expansion coefficient for short. The expansion coefficient α (0°C-300°C) is tested for transparent glass ceramics in accordance with the national standard "GB / T7962.16-2010".
[0132] The optical and mechanical indicators of the reinforced glass ceramics are tested as follows (at least 10 samples of the above size specifications are tested and the average value is taken):
[0133] 1. Transmittance test
[0134] The average transmittance (i.e. visible light transmittance) in the wavelength range of 380nm to 800nm was tested using a PerkinElmer Lambda UV-visible spectrophotometer in accordance with GB / T40415 standard.
[0135] 2. Haze test
[0136] The test was conducted using a Konica Minolta spectrophotometer CM-3600A. The light receiving optical system was transmission, the spectroscopic method was a diffraction grating, the wavelength range was 360-960nm, the wavelength interval was 10nm, the illumination source was a pulsed xenon lamp X4, the ambient temperature of the instrument was 24°C, and the air humidity was 40%.
[0137] 3. Color control LAB value B value test
[0138] LAB is a color model based on physiological characteristics, where L represents brightness, A includes colors from dark green to gray to bright pink, and B includes colors from bright blue to gray to yellow. The B value in LAB can represent the deviation between yellow and blue of an object. Tested by Konica Minolta Spectrophotometer CM-3600A.
[0139] 4. Test of mechanical properties of reinforced glass ceramics
[0140] CS: After chemical strengthening of glass ceramics, alkali metal ions with smaller radius are replaced by alkali metal ions with larger radius. Due to the crowding effect of alkali metal ions with larger radius, compressive stress is generated on the surface of strengthened glass ceramics, which is obtained by stress meter test and the unit is MPa.
[0141] DOL: Depth of compressive stress, or depth of compressive stress layer, is the distance from any surface of the strengthened glass ceramic to the position close to the surface where the compressive stress is zero, obtained by stress meter testing, and the unit is μm. Using the stress meter SLP-2000 of Japan Orihara, the test method is referred to the national standard GB-T 18144-2008 "Glass Stress Test Method" to test the depth of compressive stress layer (DOL) and surface compressive stress (CS) of strengthened glass ceramics.
[0142] 5. Four-point bending test
[0143] A microcomputer-controlled electronic universal testing machine is used, with sample specifications of 50mm*50mm*0.7mm or less in thickness, to test the reinforced glass-ceramics in accordance with ASTMC158-2002 standard.
[0144] 6. Extrusion performance test
[0145] Place the reinforced glass ceramic on the bottom ring of the tensile testing machine (LT-850A), start the test software, and set the moving speed of the extrusion rod (rod diameter 8mm, indenter arc radius 10mm) to 50mm / min. Click to start the test, and the extrusion rod will apply force to the center of the reinforced glass ceramic piece to be tested at the set moving speed until the reinforced glass ceramic cracks and breaks. The test software will automatically read the force (N) when the reinforced glass ceramic breaks as the test result. Take 10 reinforced glass ceramic samples in the same state for testing and take the average value of the test results.
[0146] 7. Impact resistance overall drop test
[0147] The test method is: among multiple identical reinforced glass-ceramic samples, the ratio of the sum of the measured sandpaper drop heights of each sample and the number of reinforced glass-ceramic samples is used to characterize the drop resistance of the reinforced glass-ceramic.
[0148] The specific test process is: take at least 10 pieces of the same reinforced glass ceramic samples for testing each time to obtain the average sandpaper drop resistance height. Among them, the test method for the sandpaper drop resistance height of each reinforced glass ceramic sample is:
[0149] (1) Stick 80-grit sandpaper on the lower surface of a 200g model machine and place the model machine on a green LT-SKDL-CD drop machine.
[0150] (2) Place a 50mm*50mm*0.7mm long, wide and thick reinforced glass-ceramic sample to be tested directly under the model machine, with the reinforced glass-ceramic sample facing the sandpaper, and drop the model machine at a certain drop height to impact the reinforced glass-ceramic sample directly under the model machine. If the reinforced glass-ceramic sample does not break, the drop height of the model machine is increased according to a certain rule. For example, the drop height starts from 40cm, and the reinforced glass-ceramic sample is dropped once. If it does not break, increase the height by 10cm each time and drop again until the reinforced glass-ceramic sample breaks.
[0151] (3) The last drop height of the strengthened glass-ceramic sample when it is broken is recorded as the anti-sandpaper drop height. For example, if the drop height when it is broken is 100 cm, then the anti-sandpaper drop height of the sample is 90 cm.
[0152] The results of the above tests are shown in Table 4 below:
[0153] Table 4
[0154]
[0155]
[0156] The reinforced glass ceramic provided by the present invention is obtained by chemically strengthening transparent glass ceramic twice, so it can have excellent mechanical properties. The mechanical properties of the chemically strengthened transparent glass ceramic are affected by the content of Li ions and Na ions in the glass phase. The content of lithium oxide in the raw material components in Example 6 is relatively large, so the mechanical properties of the reinforced glass ceramic are better than those of the reinforced glass ceramics in other embodiments.
[0157] Since the increase of the content of MgO, ZrO2 and B2O3 in the transparent glass-ceramics will reduce its thermal expansion coefficient, the linear thermal expansion coefficient of the transparent glass-ceramics in Examples 5 and 6 is relatively high.
[0158] As the crystallinity increases, the compression pressure of the strengthened glass-ceramics increases. Therefore, the maximum compression pressure values of the strengthened glass-ceramics in Example 5 and Example 3 are both relatively large.
[0159] Generally, the four-point bending strength of glass ceramics is affected by many factors. For example, chemical strengthening greatly improves the four-point bending strength of glass ceramics. At the same time, low content of network formers and high content of alkali metals and alkaline earth metals will also reduce the four-point bending strength of the transparent glass ceramics. The crystallinity of the strengthened glass ceramics in Example 5 and Example 3 of the present invention is higher, and because the content of alkali metals and alkaline earth metals is less than that of other embodiments, the four-point bending strength of the strengthened glass ceramics in Example 5 and Example 3 is higher.
[0160] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.
Claims
1. A transparent glass ceramic, characterized in that: In terms of molar percentage, the following raw materials are included: SiO2 42.0-52.0%; Al2O3 12.0-23.5%; Na2O 15.0-23.5%; K2O 0-1.0%; Li2O 3.0-9.0%; B2O3 3.0-8.0%; ZrO2 0.5-2.0%; TiO2 0-1.0%; P2O5 1.0-3.0%; MgO 0.5-2.0%; CaO 0-2.0%; SnO2 0.1-0.5%; At least one of the following relationships must also be satisfied: 1) 75% ≤ Al2O3 / Na2O ≤ 100%; 2)20%≤(Na2O+Li2O)≤30%; 3)2.0%≤(ZrO2+TiO2+P2O5)≤6.0%; The linear thermal expansion coefficient α of the transparent glass ceramic in the temperature range of 0°C-300°C is ≤100*10 -7 ℃-1.
2. The transparent glass ceramic according to claim 1, characterized in that: The raw material of the transparent glass ceramic further includes a clarifier with a molar percentage of 0.1-1.0%, and the clarifier includes at least one of NaCl, Sb2O3, As2O3, nitrate, and sulfate.
3. The transparent glass ceramic according to claim 1, characterized in that: The transparent glass ceramic has crystals with an average grain size ranging from 30 to 70 nm and a crystallinity of 25 to 55%. The crystal phases of the crystals are one or more of sodium nepheline, triclinic nepheline, sodium silicate and zirconium oxide.
4. A method for preparing a reinforced glass ceramic, characterized in that: The following steps are involved: S1. Mixing, melting, clarifying, molding and annealing the raw materials of the transparent glass-ceramic according to claim 1 or 2 according to a proportion to obtain a base glass, wherein the molding method is selected from one of a float method, an overflow method, a roller pressing method and a continuous melting casting method; S2, performing nucleation and crystallization treatment on the base glass to obtain transparent glass ceramics, wherein the nucleation temperature is 500-545° C., and the nucleation time is 120-360 min; the crystallization temperature is 600-700° C., and the crystallization time is 15 min-120 min; S3, shaping, cutting, grinding and polishing the transparent glass ceramic to obtain a glass ceramic sheet, and immersing the glass ceramic sheet in molten nitrate for chemical strengthening twice to obtain the strengthened glass ceramic; The two chemical strengthening steps include: The glass ceramic sheet is placed in a mixed molten salt of NaNO3 and / or KNO3 in a molten state at 420-480°C and immersed for 2-10 hours to obtain a first chemically strengthened glass ceramic; and the first chemically strengthened glass ceramic is placed in a molten salt of KNO3 in a molten state at 380-420°C and immersed for 15-60 minutes to obtain the strengthened glass ceramic.
5. A reinforced glass ceramic, characterized in that: The reinforced glass ceramic is prepared by the preparation method of claim 4.
6. The reinforced glass ceramic according to claim 5, characterized in that: The depth DOL of the surface stress layer of the reinforced glass-ceramic is 110 μm≤DOL≤175 μm; the surface compressive stress CS of the transparent glass-ceramic is greater than 700 MPa, and the CS_50 value is greater than or equal to 450 MPa; the four-point bending strength M of the reinforced glass-ceramic is greater than or equal to 750 MPa.
7. The reinforced glass ceramic according to claim 5, characterized in that: When the thickness of the reinforced glass ceramic is less than 1 mm, the transmittance of visible light of 400 nm to 780 nm is greater than or equal to 86%, the haze is less than or equal to 0.18%, and the B value range in the Lab color model is: 0.60≤|B|≤1.
0.
8. The reinforced glass ceramic according to claim 5, characterized in that: The maximum extrusion pressure that the reinforced glass ceramic can withstand is ≥15Kgf.
9. The reinforced glass ceramic according to claim 5, characterized in that: When the thickness of the reinforced glass ceramic is 0.70 mm, under the condition of 80-mesh sandpaper and directional impact with a load of 200 g, the reinforced glass ceramic can withstand a height of ≥180 cm and an impact energy of ≥0.30 joule.
10. Use of the reinforced glass ceramic according to any one of claims 5 to 9 in consumer electronic products or vehicle-mounted display screens.